The Combined Effect of Glass and Plastic Waste on Concrete Properties: Experimental Study - Abdelli, Houssam Eddine; Kennouche, Salim; de Aguiar, José Luis Barroso; Jesus, Carlos (Periodica Polytechnica Civil Engineering, 2024)
Industrial waste, including glass and plastic, has become widespread in recent years, harming the nature and environment in which we live. Recycling this waste in concrete appears to be one of the best solutions because of its economic and environmental benefits. In this study, the performance of concrete containing plastic waste in the form of fibers and glass waste as a partial replacement for cement was investigated. The effects of both wastes on workability and air content were studied for fresh concrete mixes, as well as their impact on the chloride penetration and carbonation resistance of hardened concrete. The effect of elevated temperature on the compressive strength, weight loss, and ultrasonic pulse velocity of the different mixes was also tested. The results showed that the combination of two wastes in the same mixture contributed to an improvement in the resistance to chloride penetration by 20.5% in the long term. The addition of glass powder to concrete increases the depth of carbonation, whereas the inclusion of plastic fibers reduces the depth of carbonation.